The discovery learning model to improve students' mathematical connection ability in exponential material - Binti Khoiriyah; Restu Lusiana; Sri Wahyu Utami (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
Connection ability is one of the mathematical skills standards that students must possess. Mathematical connection ability is the capability to relate mathematics to other fields of study as well as to mathematics itself. In the mathematics instruction for Class X MP 2, based on the results of an initial assessment, it was found that only 20% of students had a sufficiently good connection ability, while the remaining 80% lacked this skill. This study aims to examine the effectiveness of using the discovery learning model to improve the mathematical connection ability of Class X students at SMK Negeri 5 Madiun in exponent material. The study uses a Classroom Action Research (CAR) method, conducted over two cycles. The subjects of the study were 31 students from Class X MP 2 at SMK Negeri 5 Madiun. The study was conducted through several stages in each cycle, namely planning, action, observation, and reflection. The results of this study showed an increase in students' mathematical connection abilities through the application of the discovery learning model. Learning using the discovery learning model in mathematics for Class X MP 2 at SMK Negeri 5 Madiun can enhance students' mathematical connection abilities from 46.67% in the pre-cycle, 68.33% in Cycle I, to 78.3% in Cycle II.